Opportunities and Challenges of the Korea–Indonesia CEPA in Bilateral Trade and Investment - Yumitro, Gonda; Mutiara Deniar, Shannaz; Oktaviani, Sukma (Sospol, 2025)
This article aims to assess the strategic benefits of CEPA for both countries while identifying potential obstacles in its execution. Despite its significance, limited academic attention has been devoted to evaluating the real impact of CEPA beyond formal diplomatic agreements. A qualitative approach was used, utilising secondary data from academic journals, the Scopus database, and relevant news sources. The analysis was conducted by mapping key themes and relationships in the literature using VOS Viewer and assessing the logical structure and citation quality through the Typeset platform. The findings reveal that CEPA offers significant opportunities for expanding export markets, increasing foreign direct investment, and promoting technology transfer and human resource development. For South Korea, the agreement provides broader access to industrial raw materials, while for Indonesia, it presents the potential to strengthen the agricultural, manufacturing, and digital sectors. However, challenges such as global economic uncertainty, disparities in local industrial competitiveness, geopolitical tensions, and legal certainty remain critical issues. These findings contribute to the broader discourse on international economic relations and offer valuable insights for formulating sustainable bilateral trade and investment policies.